Structured air lasing of N2 + - Jingsong Gao; Xiang Zhang; Yang Wang; Yiqi Fang; Qi Lu; Zheng Li; Yi Liu; Chengyin Wu; Qihuang Gong; Yunquan Liu; Hongbing Jiang (Communications Physics, 2023)
Abstract Air lasing is a simple and promising technique to efficiently produce coherent light in the atmosphere. Yet, its capability to obtain structured light like optical vortices or vector beams is still unexplored. Here, we demonstrate the generation of vortex superfluorescent radiation with the same orbital angular momentum as the pump beam, obtained via N2 + lasing by focusing a vortex pump beam on N2 gas. The vortex superfluorescence is amplified without altering the vorticity when seeded by a Gaussian beam, in which the vortex pump beam transfers the spatial spiral phase into the N2 + gain medium and the N2 + lasing obtains the phase information. The same mechanism is applied for a vector pump beam, turning the Gaussian seed into an amplified cylindrical vector beam. We corroborate our mechanism for generating vectorially structured light via air lasing with numerical calculations. This work provides a promising approach to generating structured light via superfluorescence.